Metal-Chelated Polymer Nanodiscs for NMR Studies - Hardin, Nathaniel Z. (Angew Chem Int Ed Engl, 2019)
Paramagnetic relaxation enhancement (PRE) is commonly used to speed up spin lattice relaxation time (T(1)) for rapid data acquisition in NMR structural studies. Consequently, there is significant interest in novel paramagnetic labels for enhanced NMR studies on biomolecules. Herein, we report the synthesis and characterization of a modified poly(styrene-co-maleic acid) polymer which forms nanodiscs while showing the ability to chelate metal ions. Cu(2+)-chelated nanodiscs are demonstrated to reduce the T(1) of protons for both polymer and lipid-nanodisc components. The chelated nanodiscs also decrease the proton T(1) values for a water-soluble DNA G-quadruplex. These results suggest that polymer nanodiscs functionalized with paramagnetic tags can be used to speed-up data acquisition from lipid bilayer samples and also to provide structural information from water-soluble biomolecules.